Complete chloroplast genome sequence and phylogenetic analysis of Chimonobambusa sichuanensis (Bambusoideae). Issue 3 (4th March 2021) - Zhao, Wanqi; Cao, Binbin; Yang, Guangyao; Zhang, Wengen; Yu, Fen
Abstract: Chimonobambusa sichuanensis is an ornamental shrubby bamboo endemic to southern China. In this study, the complete chloroplast genome (cpDNA) sequence of Chimonobambusa sichuanensis was first reported. The cpDNA is 139, 594 bp in length, including a small single-copy (SSC) region of 12, 820 bp and a large single-copy (LSC) region of 83, 196 bp, which were separated by a pair of inverted repeat (IR) regions of 21, 789 bp. The genome contains 140 genes, consisting of 93 protein-coding genes, seven ribosomal RNA (rRNA) genes, and 40 transfer RNA (tRNA) genes. The phylogenetic analysis showed that C. sichuanensis is highly clustered in the Phyllostachys clade, sister to C. tumidissinoda .